An analysis of skin cancer in albinos in ibadan (2015)
Context: Skin cancers are common among albinos living in Africa. Deleterious effect of ultraviolet rays from sunlight and nearness to the equator places the African Albinos at risk for skin cancer. Aims: This study aims to present skin cancers in albinos as seen by a plastic surgeon, sensitize the public to the magnitude of dangers that albinos are exposed to, highlight the challenges faced in their management and suggest strategies for improved outcomes. Settings and Design: A retrospective review of skin cancers among albinos was conducted at the University College Hospital, Ibadan, Nigeria. Methods and Material: The charts, operation and cancer registry records of all albinos referred to a plastic surgery division over a ten year period was reviewed. Demographic data and relevant information relating to skin lesions were extracted. Statistical Analysis: Descriptive analysis was done with the aid of statistical package for social sciences (SPSS) version 20. Results: Nineteen patients with fifty nine skin lesions comprising 13 males and 6 females were reviewed. Mean age of the patients was 33.6 (SD 12.8) years, 50% were unmarried, over 90% were Christians and 44% were not employed. The lesions were on the face in 84.6% while scalp and neck lesions were present in 36.8 and 31.6% of patients respectively. In 73.7% of the patients, the lesions were advanced. Basal cell carcinoma and squamous cell carcinoma were of equal proportion. Conclusions: Albinos in Nigeria should be exposed to public health intervention to reduce the incidence of skin cancers through targeted public health educational programmes; structured multicenter and population based research, surveillance, and improved access to healthcare.